A National Public Sphere? Analyzing the Language, Location, and Form of Newspapers in Finland, 1771–1917 - Marjanen J; Vaara V; Kanner A; Roivainen H; Mäkelä E; Lahti L; Tolonen M (Universiteit Gent, 2025)
This article uses metadata from serial publications as a means of modelling the historical development of the public sphere. Given that a great deal of historical knowledge is generated through narratives relying on anecdotal evidence, any attempt to rely on newspapers for modeling the past challenges customary approaches in political and cultural history. The focus in this article is on Finland, but our approach is also scalable to other regions. During the period 1771–1917 newspapers developed as a mass medium in the Grand Duchy of Finland within two imperial configurations (Sweden until 1809 and Russia in 1809–1917), and in the two main languages – Swedish and Finnish. Finland is an ideal starting point for conducting comparative studies in that its bilingual profile already includes two linguistically separated public spheres that nonetheless were heavily connected. Our particular interest here is in newspaper metadata, which we use to trace the expansion of public discourse in Finland by statistical means. We coordinate information on publication places, language, number of issues, number of words, newspaper size, and publishers, which we compare with existing scholarship on newspaper history and censorship, and thereby offer a more robust statistical analysis of newspaper publishing in Finland than has previously been possible. We specifically examine the interplay between the Swedish- and Finnish-language newspapers and show that, whereas the public discussions were inherently bilingual, the technological and journalistic developments advanced at different pace in the two language forums. This analysis challenges the perception of a uniform public sphere in the country. In addition, we assess the development of the press in comparison with the production of books and periodicals, which points toward the specialization of newspapers as a medium in the period after 1860. This confirms some earlier findings about Finnish print production. We then show how this specialization came about through the establishment of forums for local debates that other less localized print media such as magazines and books could not provide.